Critical Assessment of Capital Buffers Under Basel III - Kant, Ravi; Jain, S. C. (Indian Journal of Finance, 2013)
The recent sub-prime crisis gave birth to Basel III, which stipulates the setting up of two capital buffers of 2.5% each to increase the banks’ equity in their lending business. The Capital Conservation Buffer is simply a top up over and above the stipulated capital levels of 8%. And, the discretionary Counter-Cyclical Buffer aims to dampen the credit cycle in a booming economy to reduce the systemic risks. This paper argues that on the one hand, the recoup of capital conservation buffer would be difficult once it gets depleted and on the other, the banks would find it attractive to further boost up the credit growth in order to reduce the impact of additional capital requirements. The other adverse impacts of discretionary buffers would be upsetting growth plans of the industry, caution among investors and effect on banks’ asset quality. On the contrary, the release of discretionary buffers is only leverage enhancing enabling factor and is not by itself amount to increase in cash flows and liquidity for credit growth. And, it would not positively impact the banking profitability either.